Digital Badging and the Need for Assessment Framework. (17th February 2020) - Jagger, Paul
Abstract: When it comes to evidencing skills, knowledge and experience, digital badges have indelible advantages. But, as Paul Jagger FBCS explains, there is room for improvement.